PENGARUH PEMBERIAN BEBERAPA KONSENTRASI PUPUK MAJEMUK BERTEKNOLOGI NANO TERHADAP PERTUMBUHAN DAN HASIL TIGA VARIETAS TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Endah Nur’aeni; Kartina Kartina; Susiyanti Susiyanti (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2020)
This research was conducted in Cikayas Village, Angsana Sub district, Pandeglang Banten Regency from December 2019 until February 2020. The first research was using randomized completely block design with factorial design group, consisting two factors, the first factor was concentration of nano-based compound fertilizer consisting of four levels: without nano-tech fertilizers, 2.5 ml/L, 5 ml/L, 7.5 ml/L. The second factor was:variety consisting of three levels: Bima Brebes, Maja Cipanas, Trisula. The experiment was repeated three times, the whole experimental unit was 36. The results showed that the application of nano-tech compound fertilizer with 5 ml/L gave the best growth and yield to the height parameters of four WAP (42.33 cm), number of leaves four WAP (39.33 cm) and five WAP (42.67 strands), and tuber weights without roots and leaves per clump (37.19 g). Bima Brebes variety gave the best growth and yield to the height parameters one WAP (10.74 cm), two WAP (25.55 cm), 3 WAP (35.27 cm), 4 WAP (42.63 cm) and 5 WAP (47.33 cm), and tuber weights without roots and leaves per clump (36.29 g). There was no interaction between several Concentrations of Nano-tech Compound Fertilizer and varieties to all parameters observed.